Parents’ Behaviour in Storytelling and Attaining Information of Child Growth and Development - Agustin Rahmawati; Yesika Maya Ocktarani (Universitas Muhammadiyah Semarang, 2022)
Early childhood is a critical period for the development of both the physical and mental of an individual. At this age, the growth of a child needs to be monitored so parents can provide correct treatment to their child. This paper depicts parents’ behaviour in accessing information regarding their preschool children’s growth and development and in boosting their storytelling activities as media to support literacy. This claim was revealed from a study because the prevalence of stunting and malnutrition remains high in recent years. The study applied two phases to gain its data, first using questionnaires involving 51 respondents from an urban area, then continuing with focus group discussion to get more profound evidence. The results indicated that parents are close to storytelling activities with their children. They also believe that literation on child growth and development is essential. However, the finding shows that the parents tend to use social media as the source of information and storytelling activities are not related to children’s growth and development. These findings provide preliminary support for policymakers to provide sufficient information through various media. The results also offer that fact storytelling can be used as media to educate parents and children regarding child development.